Diversifikasi Buah Mangrove menjadi Produk Olahan di Desa Tanjung Tiram, Kabupaten Konawe Selatan, Sulawesi Tenggara - Jamili, Jamili; Yanti, Nur Arfa; Oetama, Dedi (Universitas Nusantara PGRI Kediri, 2021)
Tanjung Tiram village is a coastal area in the North Moramo sub-district, South Konawe District, Southeast Sulawesi which has quite high mangroves. However, the mangrove communities in the area have experienced damage in several places. Therefore, this service activity provides counseling on mangrove ecosystem conservation and training on the use of mangrove fruit into various products of economic value. The purpose of this activity is to increase the knowledge and skills of the community about the manufacture of various processed products made from mangroves fruit so that the mangrove ecosystem in the area is better preserved. The methods and approaches used in this activity are counseling and training. Community service activities in the village of Tanjung Tiram can increase community knowledge about the importance of mangrove ecosystem conservation and utilization of mangrove fruit up to 100%. Mangrove fruit processing training provided to the community was also able to improve community skills in processing mangrove fruit into flour, syrup, and scrub cosmetics up to 75%.